The Effect of Firm Size and Green Accounting on Tax Aggressiveness in Consumer Non-Cyclical Companies Listed on the Indonesia Stock Exchange in 2022–2024 - Namia Nathaniel Juliet Poyoh; Meidy Lieke Karundeng; Herold Moody Manalu (Sean Institute, 2026)
This study aims to analyze the effect of firm size and Green Accounting on tax aggressiveness in consumer non-cyclical sector companies listed on the Bursa Efek Indonesia during the 2022–2024 period. This research employs a quantitative approach using regression analysis to examine the partial and simultaneous effects of the variables.The results indicate that firm size does not have a significant effect on tax aggressiveness, suggesting that company scale is not a determining factor in tax aggressiveness practices. Green Accounting also does not have a significant effect on tax aggressiveness, indicating that the implementation of environmental accounting practices has not been able to influence corporate tax behavior. Simultaneously, firm size and Green Accounting do not have a significant effect on tax aggressiveness.These findings suggest that tax aggressiveness may be influenced by other factors beyond the variables examined in this study. This research is expected to contribute to the development of literature related to the factors influencing tax aggressiveness and serve as a reference for future research.